Rice Husks as a Biogenic Template for the Synthesis of Fe2O3/MCM-41 Nanomaterials for Polluted Water Remediation - Benzaquén, Tamara Belén (2025)
This work shows a sustainable methodology for the synthesis of biogenic materials designed for the removal and photodegradation of rhodamine B (RhB), a highly dangerous environmental pollutant that induces reproductive toxicity. The classical synthesis of MCM-41-ordered mesoporous materials was modified using biocompatible rice husk as the silica template. Iron was incorporated and the so-prepared biogenic photocatalysts were characterized by X-ray diffraction, N2 adsorption–desorption isotherms, transmission electron microscopy, diffuse reflectance UV-Vis, surface pH, cyclic voltammetry, and Fourier transform infrared spectral analysis of pyridine adsorption. The photocatalytic performance of the materials was evaluated following the removal by adsorption and the photon-driven degradation of RhB. The adsorption capacity and photocatalytic activity of the biogenic materials were correlated with their properties, including iron content, texture, surface content, and electrochemical properties. The best biogenic material boosted the degradation rates of RhB under UV irradiation up to 4.7 and 2.2 times greater than the direct photolysis and the benchmark semiconductor TiO2-P25. It can be concluded that the use of rice husks for the synthesis of biogenic Fe-modified mesoporous materials is a promising strategy for wastewater treatment applications, particularly in the removal of highly toxic organic dyes.